Does Urbanisation Matter? A Temporal Analysis of the Socio‐demographic Gradient in the Rising Adulthood Overweight Epidemic in China, 1989–2009. Issue 1 (16th July 2015) - Fu, Qiang; Land, Kenneth C.
Abstract: Using eight successive waves of the China Health and Nutrition Survey, this study applies hierarchical age–period–cohort models to investigate the rising prevalence rates of adulthood overweight in China. We find that overweight prevalence rates increase throughout adulthood until the early 50s. Period effects are very strong with a virtually monotonic increase from 1989 to 2009. Yet, as posited by the reversal hypothesis (a diminishing positive association between overweight prevalence and socioeconomic status alongside development), this increase is levelling off or absent in most recent survey waves for women, urban residents, and individuals with higher educational attainment. Most importantly, substantial period variations are explained by rapid urbanisation, and the period increases in overweight prevalence closely track the pace of urbanisation in China. Cohorts born in the beginning years of the Great Chinese Famine (1958–1961) have the highest overweight prevalence rates, whereas cohorts experiencing the Famine during the childhood ages of adiposity rebound (the next rise in body mass index after infancy, typically from age 5 to 7 years) are significantly less likely to be overweight. These cohort patterns lend support to the critical‐period hypothesis. Copyright © 2015 John Wiley & Sons, Ltd.